Markets, hierarchies, and hybrids in corporate insurance - Luc L. Grillet (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
The superior risk-bearing ability of commercial insurers is limited. Their comparative advantage depends on the calculability of property-liability loss distributions. Insurance contracts have their own transaction costs and these may outweigh the benefits of the commercial risk transfer. The violation of actuarial preconditions for insurability will augment these transaction costs. This increases incentives for insurance internalization and changes the organizational structures governing the market for corporate insurance. Residual risk bearing by captive and mutual forms may enhance further market exchange.
Keywords: 330